Analysis of Debt to GDP Ratio with Microeconomic Foundations: Theoretical Basis for MMT Arguments - Yasuhito Tanaka (Research in Applied Economics, 2024)
This paper examines the relationship among budget deficit, inflation rate and debt to GDP ratio from the perspective of Functional Finance Theory and MMT (Modern Monetary Theory). Using an overlapping generations model under monopolistic competition with bequest motive of consumers, mainly we will show the following results. • Under full employment with constant prices or inflation the debt to GDP ratio does not change from a period to the next period • The interest rate on government bonds should equal the nominal growth rate to achieve full employment with constant prices or inflation under balanced budget excluding interest payments on government bonds. • The inflation rate we need to maintain full employment under balanced budget excluding interest payments on government bonds is determined by the interest rate